Labile anticausatives in Jordanian Arabic - Mashaqba, Bassil; Huneety, Anas; Zuraiq, Wael; Al-Omari, Moh’D; Al-Shboul, Sabri (Lingua Posnaniensis, 2020)
This study examines the morpho-syntax of labile anticausative structures in Jordanian Arabic (JA). Although the transitive counterpart of anticausatives is marked via morphological affixes that reflect structural and lexical components in Classical Arabic and Modern Standard Arabic, a number of verbs involving causative alternation exhibit identical forms in JA (e.g., ġala [+T] ‘to CAUSE boil something’ vs ġala [–T] ‘to BECOME boil’). Such variation poses challenges for mapping between verb morphology and its lexical semantics. To handle such variation, which is also observed cross-linguistically, we argue in favour of Schäfer (2008; 2012), Schäfer & Vivanco (2015), and Ramchand’s (2008) “causer-less” analysis over Koontz-Garboden’s (2009) “reflexive” analysis. This work further assumes the existence of a Voice phrase lacking a specifier (external argument) and assumes that Voice projection is headed by an implied Voice head (vcauser) that syntactically assigns the accusative case to its new subject and semantically encodes the internal argument and describes the resultant subevent of the verb. The work also provides an alternative solution for voice projection that lacks an explicit specifier bearing [+agent] or [+causer] feature specification. The work assumes the presence of an inchoative Voice head [vinch] introducing the Spec Voice Phrase, which encodes an inchoative resultant state of an event achieved over its theme. Contrary to Al-Qadi (2015), the present model assumes that such verbs constitute a middle position between transitive and intransitive verbs in JA but do not constitute a separate class of their own. Evidently, the correct characterization of the anticausative subclass distribution is that it surfaces wherever v is transitive as well as in intransitive volitional contexts (a non-natural class). More intriguingly, the presented material suggests that there is an ongoing process of diachronic change in spoken Arabic varieties (including JA) that amounts to the development and expansion of an inchoative class where no external or internal inchoative detransitivizing morphemes are involved. This topic, which incorporates an intriguing diachronic dimension in addition to the syntactic details, is missing from the generative literature on Arabic morpho-syntax and is potentially of sufficient interest to merit investigation.